TABOO IN BALINESE LANGUAGE SPOKEN IN MUNDEH VILLAGE: A DESCRIPTIVE QUALITATIVE RESEARCH - Satriya Wibawa, I Putu Gede; Budasi, I Gede; Ramendra, Dewa Putu (Jurnal Impresi Indonesia, 2024)
Study This aims To identify ( 1) taboo words, (2) forms of taboo words, and (3) references used in public Village Mundeh, Tabanan. Study This uses the qualitative descriptive. The data type uses primary data instrument study as a table sheet. The deep data collection study technique uses interviews with three original people, Villagin e Mundeh, with criteria that have been set. Procedure Data analysis begins with data collection, data reduction, data presentation, and writing a conclusion. Research data in the form of a taboo word in the environment Narayanan, pawing, palemahan, form taboo, and a reference from taboo the. Study This adopts a theory from Frazer (1955), which discusses taboo names and words, and a theory from Montagu (1973), which discusses oath swear. Results show that 5 data were found in the environment parhyangan, 5 in the environment palemahan, and 32 in the environment pawongan. For taboo Names, 6 data were found for words, 13 for swearing words, and reference to taboo is appropriate with theory from Laksana (2009) found data for 12 references. The conclusion from the study This shows that the most data found in the environment pawongan as many as 32 words.